An electro-tensile bioreactor for 3-D culturing of cardiomyocytes. - Zhonggang Fengcardiac tissue engineering
Cardiac tissue engineering is an emerging field that shows great potential for the treatment of heart disease. With the aim of addressing concerns on a number of the major constraints inherent to cell and tissue culturing, such as ease of cleaning and sterilization, a unique design for gel fixation, and compatibility with commercially available CO2 incubators, an electro-tensile bioreactor for 3-D culturing of cardiomyocytes in collagen gels has been developed. To the authors' knowledge, this is the first electro-mechanical bioreactor system to simulate the electrical and mechanical response of the myocardium in vivo. In this paper, a dynamic tensile force similar to that which occurs in the cardiac cyclic action in vivo is employed. The electric stimulus is utilized not only for the simulation of in vivo electrical activity but for synchronistic pacing of the extra-mechanical stimulus with the spontaneous beating of the cultured cardiac tissue equivalent (CTE). The enhancement of contraction of the CTEs was observed using light microscopy. These results emphasize the importance of electro-tensile forces on the augmentation of CTE contractile force.
Keywords: 3-D cardiomyocyte culturing; Cardiac cyclic action; Cardiac tissue engineering; Cardiac tissue equivalent; Cell culturing; Cleaning; Collagen gels; Compatibility; Contractile force; Dynamic tensile force; Electric stimulus; Electrical response; Electro-mechanical bioreactor system; Electro-tensile bioreactor; Extra-mechanical stimulus; Gel fixation; Heart disease treatment; In vivo electrical activity; Light microscopy; Mechanical response; Myocardium; Sterilization; Tissue culturing; CO2 incubators